Implementation of ROP and EOQ in the Stock Management Information System at Panglong Siagian Bersaudara Based on Website - Disnu Panggabean; Samsudin Samsudin (Indonesian Journal of Data Science, IoT, Machine Learning and Informatics, 2025)
Advances in information and communication technology have encouraged the transformation from manual systems to digital-based systems, including in stock management. This research aims to develop a website-based stock management information system using the Reorder Point (ROP) and Economic Order Quantity (EOQ) methods for Panglong Siagian Bersaudara. ROP is used to determine reorder time, while EOQ calculates the optimal number of items that must be ordered to minimize total costs. The system was designed using the Rapid Application Development (RAD) method, resulting in a fast and structured design. The implementation results show that the system is able to increase stock management efficiency by reducing the risk of shortages or excess items, optimizing storage costs, and supporting real-time data-based decision making. With the integration of ROP and EOQ, this system provides a comprehensive solution for stock management at Panglong Siagian Bersaudara.